PENGARUH MEDIA PEMBELAJARAN STORY BOX KONTEKSTUAL TERHADAP MINAT DAN HASIL BELAJAR PESERTA DIDIK DI KELAS II - Mela Sari Sadeli; Yulianti; Romia Hari Susanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The contextual story box is considered an effective medium to improve students' interest and learning outcomes. This medium combines visual and narrative elements that capture students’ attention and enhance understanding of the material. This study aims to determine the effect of using the story box on the interest and learning outcomes of second-grade students in Pancasila Education. The research employed a quantitative approach using a quasi-experimental design with a non-equivalent control group. The sample consisted of class 2A (control) and class 2B (experimental). Data were collected through pretests, posttests, and learning interest questionnaires. The results showed an increase in students’ learning outcomes by 7.778 points and in learning interest from 64.75% to 92.88% in the experimental class. The t-test revealed a significance value of 0.02 < 0.05, indicating that the story box had a significant effect on students' interest and learning outcomes at SDN Gadang 3 Malang.